Administrative, Cognitive, and Psychological Factors that Limit the Research Process in the General Studies Directorate of the Autonomous University of Peru - LEON VERGARA, RAFAEL RENE; Cano Gamarra, Harold Walter; Campos Rosendo, Nelson Jesús; Montenegro Carrillo, Pedro Martin; Navas Gotopo, Soratna Verónica; Flores Perozo, Inés del Carmen; Pecho Rivera, María Cristina (LACCEI, 2024)
In this article, the level at which administrative, cognitive and psychological factors impact within the research process was determined in order to describe the degree to which these factors would be limiting the research activity of the teachers of the General Studies Directorate of the Autonomous University. of Peru (DEEGG-UA). The study was divided into three levels; first by a general analysis, then by dimensions and finally at the level of indicators. The results showed that time factors, lack of economic resources and the need to generate more income are the main causes that limit the research in the sample considered. It is concluded that administrative, cognitive and psychological factors are key to promoting research. It is recommended that scientific research be inserted in all subjects with products that are evident from the beginning to the end of the professional training process, as this will contribute to the enhancement of research development in the teachers of this house of higher education.